Simulation, Control and Experimental Analysis of 1,3Butadiene Purification Unit - Rahbar Rahimi; Shirin Boulaqhi; Amir Ziarifar (Iranian Journal of Chemical Engineering)
Simulation of a process and analysis of its resulting data in both dynamic and steady-state conditions are fundamental steps in understanding the process in order to design and efficient control of system as well as implementing operational cost reduction scheme. In the present paper, steady and unsteady state simulation of Amir Kabir1, 3 butadiene purification units has been done by using Aspen and Aspen Dynamic software together with the Peng- Robinson equation of state to investigate the system responses to the disturbances. In the unsteady state simulation mode; the flow rates, pressure, temperature and level (FPTL) were controlled by Proportional-Integral-Derivative (PID) controllers in the unit. Finally, transient responses to changes such as feed temperature, feed flow rates, steam flow rates and the duties of the re-boiler of columns in unit were gained. For reaching to purified 1,3 butadiene, sensitivity of the process to the fluctuations of feed temperature and on the duties of the re-boilers of the columns is noticeable .